Stable isotope record of Cibicidoides wuellerstorfi and Uvigerina perigrina of sediment core SO213/2_82-1 - Thomas A Ronge (PANGAEA, 2025)
The dataset show stable isotope data of d13C and d18O measured on benthic foraminifers, C. wuellerstorfi and U. perigrina. The samples were collected in the Bounty Trough off New Zealand during Expedition SO213/2 in 2011. The aim of this study was to reconstruct the dynamics of Southern Ocean water masses on glacial-interglacial timescales.